Who are the potential consumers of organic fruits and vegetables in Central Chile? : a CHAID approach - Adasme-Berríos, Cristian (2015)
The demand for organic fruits and vegetables (F&V) is growing worldwide, creating market opportunities for developing countries as major suppliers. However, most export-oriented developing countries such as Chile have an undeveloped domestic market for organic products. This article identifies the segments of potential consumers of organic F&V in Central Chile using an exploratory CHAID model. A questionnaire was administered by surveying a random sample of 425 F&V consumers in central Chile. The results of the CHAID model suggest two segments of potential consumers of organic F&V. Both groups show awareness of the concept of organic food. Additionally, the first segment perceives organic agriculture to have ethical benefits to the society and considers organic F&V as healthy and nutritious; this group has a probability of over 80% to consume organic F&V. The second segment shows less awareness of the ethical benefits to society and its probability of consuming organic F&V depends on family income level. We discuss major implications for further studies on organic consumers.